Live Low-Train High in elite athletes: A case study of a responder and non-responder - Hamlin, M. J. (Sport and Exercise Science New Zealand Conference, 2013, 2013)
An increasingly popular method of altitude training is the "Live Low-Train High" (LLTH) technique where athletes live at or near sea level but train under hypoxic conditions similar to altitudes of 2500-5000m. However, the performance benefits of altitude training show considerable individual variability and therefore such training may not benefit all athletes. It has been suggested the introduction of altitude training can increase the stress in some athletes causing them to become overstressed, resulting in a detrimental training effect. Close monitoring of athletes especially at stressful times is therefore important and heart rate variability (HRV) has been suggested as a possible measure of physiological stress in athletes. The aim of this study was to use data from two elite New Zealand athletes as case studies for the use of LLTH. Two elite athletes (current or past New Zealand cycling champions) were monitored during a 2-4 week LLTH training bout (total days spent at altitude was 15-16 days totalling 23-24 hours in hypoxia). During LLTH athletes breathed hypoxic gas from a Douglas bag set-up with an FIO2 set to produce arterial oxygen saturations of 85% (week 1) to 78-75% (week 2-4) while exercising on their own bikes attached to a stationary training ergometer. Each athlete completed 90 min of hypoxic training per session which consisted of endurance (60-70% of heart rate reserve [HRR]) and higher intensity work (70-85% HRR) in conjunction with their normal training. LLTH training was conducted approximately 3-4 days per week. Pre and post-training blood tests were completed along with performance tests that were designed not to disrupt training schedules (progressive submaximal tests measuring either blood lactate or power production). During training perceived stress, fatigue and training performance were monitored daily, along with HRV (the root mean square of the successive differences in the last 5 min of a 10 min supine resting heart rate [rMSSD]) on a bi-weekly basis. The athlete that benefited from LLTH training (responder) showed substantial increases in haemoglobin (8%), and haematocrit (2%), had little change in HRV (3.5%) or submaximal exercise performance (1%) compared to baseline. On the other hand, the athlete that did not benefit from LLTH (non-responder) showed no substantial increase in haemoglobin (0%), or haematocrit (1%), had a substantial decrease in HRV (-52%) along with a decrease in submaximal exercise performance (-4.5%) compared to baseline. The additional stress of altitude training along with the normal stressful lives of elite athletes may bring about a period of maladaptation and performance decrement. Close monitoring of athletes during altitude training is advised.